Evaluation and Susceptibility Pattern of Staphylococci Isolated From Clinical Specimens in POF Hospital, Wah Cantt. - Lubna Ghazal, Saba Mushtaq, Sohail Ashraf, Saima Rafique, Muhammad Bilal, Naila Iqbal, Lubna Ghazal, Saba Mushtaq, Sohail Ashraf, Saima Rafique, Muhammad Bilal, Naila Iqbal (Journal of Rawalpindi Medical College, 2022)
Objective: To determine the frequency and antibiotic susceptibility pattern of Staphylococcus aureus and coagulase negative staphylococci isolated from clinical specimens as a result of culture and sensitivity. Materials & Methods: This cross sectional study was carried out in POF Hospital Microbiology laboratory from January 2019 to September 2020. One hundred and eighty four staphylococci isolated from clinical specimens were processed as per standard methodology. Results: Out of 148, methicillin resistant S.aureus and methicillin resistant coagulase negative staphylococci were 38.04% and13.04% respectively. Infections caused by Methicillin resistant staphylococcal isolates were higher among the age group 31-40 years (71.4%, OR=2.68). Out of thirty expired patients, 53.3% had been infected with methicillin resistant staphylococcal infections. The methicillin resistant staphylococci were most frequent in miscellaneous category of clinical specimens (80.0%, OR=4.63). The susceptibility analysis revealed that methicillin resistant staphylococci are 100% resistant to penicillin, meropenem and amoxycillin-clavulanate (p=0.000). A significant association of methicillin resistance was also noticed against amikacin (p=0.002), ciprofloxacin (p=0.001), clindamycin (p=0.005) and erythromycin (p=0.000). Moxifloxacin, linezolid and vancomycin are the most effective choice for infections caused by methicillin resistant staphylococci. Conclusions: The methicillin-resistant staphylococci are highly resistant to commonly prescribed oral as well as injectable antibiotics. Establishment and implementation of infection control policies are required to combat the grave situation of increasing antibiotic resistance.